2012
DOI: 10.1097/iae.0b013e31825c1c0c
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcome Correlates With Inner Macular Volume in Eyes With Surgically Closed Macular Hole

Abstract: Purpose To determine the macular morphologic features that correlate best with visual outcome in eyes with surgically closed idiopathic macular hole. Methods Transversal observational case series of 24 eyes (22 subjects) imaged postoperatively using high-resolution Fourier domain optical coherence tomography (FD-OCT). Total and inner macular volume for central 3 mm area, central foveal thickness, and size of foveal inner segment–outer segment junction abnormality were correlated with best-corrected visual ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…Improved RPE band integrity on successful MH surgery was also not found to be associated with final BCVA scores; however, re-establishment of ELM, EZ, and COST line was associated with a better visual prognosis. On the contrary, some published studies have reported a negative correlation between preoperative MH dimensions measured using OCT and postoperative visual recovery (21)(22)(23)(24)(25)(26) . The MH base dia meter, which was measured at the RPE level, and the minimum diameter of the hole, which represented the shortest extent of MH, appear to constitute prognostic factors for postoperative anatomical and functional outcomes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Improved RPE band integrity on successful MH surgery was also not found to be associated with final BCVA scores; however, re-establishment of ELM, EZ, and COST line was associated with a better visual prognosis. On the contrary, some published studies have reported a negative correlation between preoperative MH dimensions measured using OCT and postoperative visual recovery (21)(22)(23)(24)(25)(26) . The MH base dia meter, which was measured at the RPE level, and the minimum diameter of the hole, which represented the shortest extent of MH, appear to constitute prognostic factors for postoperative anatomical and functional outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…Pilli et al (26) recommended performing ILM peeling to achieve a better visual outcome because a close correlation between inner macular volume and BCVA was observed. In our study, although no statistical correlations were found between MHV and postoperative BCVA or MHV and disease recurrence, a negative correlation was present between MHV and CMT measured at the last follow-up (p=0.04, r=-0.383).…”
Section: Discussionmentioning
confidence: 99%
“…These advances include the ability to automatically measure retinal nerve fiber layer (RNFL) and GC-IPL. [26][27][28][29] In addition, advances have helped in the development of en face OCT. En face OCT is an imaging modality that facilitates the assessment of retinal structures transversely and allows layer-by-layer retinal visualization. [30][31][32][33] Alkabes et al 34 examined the appearance of DONFL using en face SD-OCT and observed multiple dark dots along the course of RNFL.…”
mentioning
confidence: 99%
“…60 On the other hand, loss of its structural role or secondary collateral nerve fiber layer loss during removal may be detrimental. [60][61][62] In a recent large meta-analysis of 5480 cases, Rahimy and McCannell concluded that ILM peeling at the time of surgery significantly reduces the likelihood of the hole reopening but without better postoperative best-corrected visual acuities. 63 (I++, Good quality, Strong recommendation) 65 Brooks et al reported an 18% difference in favor of ILM peeling with a statistically significant difference in visual acuity between the peeling and non-peeling groups.…”
Section: P189mentioning
confidence: 99%